The Executive Guide to Corporate Restructuring - Pérez Lubián, Francisco J. (Colección de libros electrónicos de ULoyola, 2014)
In recent years the continuity of many firms has been achieved by restructuring, a task which takes up a great deal of senior management's time. Written for busy managers and executives, this book is a practical guide to the process of restructuring, covering both debt and operational restructures.